PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN (STUDI KASUS PADA PT. BANK PERKREDITAN RAKYAT SHINTA DAYA) - Chaisunah, Chaisunah; Muttaqiyathun, Ani (Jurnal Fokus Manajemen Bisnis, 2011)
This research entitled compensation and work environment influence job satisfaction of employees of PT. Bank Perkreditan Rakyat Shinta Daya. Basic research is whether the compensation and work environment has a significant impact on job satisfaction. The purpose of this study was to determine whether the compensation and work environment has a significant impact on job satisfaction of employees of PT. Bank Perkreditan Rakyat Shinta Daya either partially or in unison.    In this research, compensation (X1) and the working environment (X2) as independent variables and job satisfaction (Y) as the dependent variable. The study involved PT. Bank Perkreditan Rakyat Shinta Daya as objects of research hypothesis is the influence of compensation and work environment on job satisfaction. The population in this study are all permanent employees in PT. Bank Perkreditan Rakyat Shinta Daya.  The sample is selected by using the technique of saturated samples (census), which totaled  80.